Testing of a Stand for Analysis of Drilling Mud Friction Factor - Stanisław Stryczek; Rafał Wiśniowski; Krzysztof Skrzypaszek (Acta Montanistica Slovaca, 2006)
A concept and realization of a universal laboratory stand for analyzing hydromechanical effects accompanying the drilling mud flow are presented in the paper. Requirements for basic technical subassemblies of the stand are defined. The principles of a flow meter, pressure converters and digital data readers are presented. Then a scheme of a laboratory stand, its principle and procedure are discussed. The process of stand testing through an empirical determination of the Faning friction factor for Newtonian fluids is presented and compared with literature data.